Prevalence of the metabolic syndrome, insulin resistance index, leptin and thyroid hormone levels in the general population of Mérida (Venezuela) - Uzcátegui, Euderruh; Valery, Lenin; Gómez, Roald; Marquina, David; Baptista, Trino (Investigación Clínica, 2015)
Ver resumen PDF.